Dynamic Effects on Fatigue Life of Cement Treated Crushed Rock - Yeo, Yang Sheng; Jitsangiam, Peerapong; Nikraz, Hamid (Australian Geomechanics Society, 2011)
Fatigue life prediction of cement treated crushed rock is not a well understood concept in pavement engineering. The complexity to understand fatigue response of pavement lies not only in the structural model or the defining criteria for measurement, but also includes the testing regime to be adopted. Despite the well established testing methodologies for asphalt, minimal literature and standardised laboratory regimes exists for cemented basecourse. Fatigue testing of these materials is complicated by a multitude of variables that has to be considered in order to provide meaningful and representative data for design. Recent studies have been undertaken in Australia recently to characterise the fatigue phenomenon using a four point bending test setup by Austroad. Nevertheless, the loading frequency on fatigue life has not been addressed explicitly. A laboratory investigation to assess the loading frequency during pavement testing is undertaken. The paper presents the challenges and resultsachieved from test.